Are E-cigarettes associated with postpartum return to smoking? Secondary analyses of a UK pregnancy longitudinal cohort. Issue 4 (12th April 2022) - Orton, Sophie; Taylor, Lauren; Laing, Libby; Lewis, Sarah; Ussher, Michael; Coleman, Tim; Cooper, Sue
Abstract : Objectives: Postpartum return to smoking (PPRS) is an important public health problem. E-cigarette (EC) use has increased in recent years, and in a contemporary UK pregnancy cohort, we investigated factors, including ECs use, associated with PPRS. Design: Secondary analyses of a longitudinal cohort survey with questionnaires at baseline (8–26 weeks' gestation), late pregnancy (34–36 weeks) and 3 months after delivery. Setting: 17 hospitals in England and Scotland in 2017. Participants: The cohort recruited 750 women who were current or recent ex-smokers and/or EC users. A subgroup of women reported being abstinent from smoking in late pregnancy (n=162, 21.6%), and of these 137 (84.6%) completed the postpartum questionnaire and were included in analyses. Outcome measures: Demographics, smoking behaviours and beliefs, views and experience of ECs and infant feeding. Results: 35.8% (95% CI 28% to 44%) of women reported PPRS. EC use in pregnancy (adjusted OR 0.34, 95% CI 0.13 to 0.85) and breast feeding (adjusted OR 0.06, 95% CI 0.02 to 0.24) were inversely associated with PPRS, while household member smoking at 3 months post partum was positively associated with PPRS (adjusted OR 11.1, 95% CI 2.47 to 50.2). Conclusion: EC use in pregnancy could influence PPRS. Further research is needed to confirm this and investigate whether ECs could be used to prevent PPRS.